Theological reflections on compadrazgo - Sánchez Arjona, Rodrigo (1973)
At the annual meetings of the I.P.A. We have often spoken of the compadrazgo spread among our peasants everywhere; some praise it, most would like to see it extinguished once and for all, because they see in it a form of social exploitation. The pages of the Allpanchis Magazine give us the opportunity to reflect on this important phenomenon in the lives of our peasants in the Sierra. Where does compadrazgo have its roots? Is it an institution that comes only from the socio-economic infrastructures or, on the contrary, is it also supported by a whole rich range of an ancestral subconscious and an existential theology planted in our town by the missionaries of the colony?